Social Support, Mindfulness, and Job Burnout of Social Workers in China - Xie, Xiaoxia; Zhou, Yuqing; Fang, Jingbo; Ying, Ganghui (Frontiers in Psychology, 2022)
In the last twenty years, amid extensive social and economic reforms, China’s social structure and community life have changed considerably. A large number of social workers are needed to provide many more social services to community residents. The central government has issued many policies to rapidly develop human service organizations and increase the number of social workers. Thus, by the end of 2019, the number of social workers has reached more than 1.5 million in China. At the same time, local governments have issued many policies to promote an increase in the number of social workers. According to statistics from the Chengdu Civil Affairs Bureau, from 2010 to 2021, the number of social workers in Chengdu City increased, remarkably, from 553 to 17,622. Although the number of social workers has increased rapidly, some problems still exist. According to a survey by the Chengdu Social Workers Association, the turnover rate of social workers has reached approximately 20% in Chengdu City in 2018. Therefore, we aim to determine what influences social workers’ job burnout. Through regression analysis and mediation effect tests, we found the following: First, when controlling for gender, age, education and workday, social support of social workers had a significant negative impact on job burnout (β=-0.376). Second, the mindfulness of social workers had a significant negative impact on job burnout (β=-0.320). Third, the mindfulness of social workers played a mediating role between social support and job burnout. The mediating effect was -0.116 (p<0.001). Fourth, among the three dimensions of social support, mindfulness played a partially mediating role in family support and other support. The mediating effect between other support, which is the support from leaders and colleagues, and job burnout was the strongest, with a mediating effect of -0.109 (p<0.001). In other words, the support provided by agency leaders and colleagues can maximize the level of mindfulness of social workers, thereby reducing social workers’ job burnout most effectively. We can thus reduce social workers’ job burnout by improving their level of mindfulness and the social support for them in China.